2008
DOI: 10.1038/sj.mp.4002153
|View full text |Cite
|
Sign up to set email alerts
|

Serious obstetric complications interact with hypoxia-regulated/vascular-expression genes to influence schizophrenia risk

Abstract: The etiology of schizophrenia is thought to include both epistasis and gene-environment interactions. We sought to test whether a set of schizophrenia candidate genes regulated by hypoxia or involved in vascular function in the brain (AKT1, BDNF, CAPON, CHRNA7, COMT, DTNBP1, GAD1, GRM3, NOTCH4, NRG1, PRODH, RGS4, TNF-a) interacted with serious obstetric complications to influence risk for schizophrenia. A family-based study of transmission disequilibrium was conducted in 116 trios. Twenty-nine probands had at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 43 publications
4
128
1
2
Order By: Relevance
“…Using the McNeil-Sj€ ostr€ om Scale, 35 we assessed exposure to hOCs in 168 healthy humans demonstrating that the relationship between hOCs exposure and BDNF rs6265 methylation is affected by rs6265 genotype. In fact, we found an interaction Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the McNeil-Sj€ ostr€ om Scale, 35 we assessed exposure to hOCs in 168 healthy humans demonstrating that the relationship between hOCs exposure and BDNF rs6265 methylation is affected by rs6265 genotype. In fact, we found an interaction Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, birth hypoxia has been associated with reduced BDNF levels in cord samples, taken at delivery, of individuals who developed schizophrenia later in life, 34 and other genetic variation of the BDNF signaling interact with early life hypoxia in affecting risk for the disorder. 35 Surprisingly, these studies failed to show a role of rs6265 in interacting with obstetric complications in affecting risk for schizophrenia. A possible explanation for these results is that epigenetic mechanisms related to these environmental factors modulate the effect of the most likely relevant functional SNP of BDNF.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a Pub Med search was carried out using the keywords "(NOS1AP OR CAPON) AND schizophrenia" as well as "NOS1 AND schizophrenia", to identify all genetic studies on NOS1AP (n=24 retrieved studies) or NOS1 (n=42 retrieved) and schizophrenic disorders. Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed.…”
Section: Meta-analysismentioning
confidence: 99%
“…Following up the studies of Brzustowicz and colleagues, both positive (Kremeyer et al, 2009;Miranda et al, 2006;Zheng et al, 2005) as well as negative Nicodemus et al, 2010;Nicodemus et al, 2008) family-based and case-control studies were published. In addition, a mutation analysis suggested that rare coding variants in NOS1AP underlie obsessive-compulsive disorder and autism (Delorme et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[111][112][113][114] In particular, recent findings show that many of the susceptibility genes identified for schizophrenia are affected by hypoxia. [115][116][117] Nicodemus and colleagues 116 performed a gene-environment interaction analysis in a family study of schizophrenia probands, siblings, and controls. The authors examined whether a set of schizophrenia candidate genes affected by hypoxia or involved in vascular function in the brain interacted with serious OCs to influence risk for schizophrenia.…”
Section: Gene-environment Intreractionmentioning
confidence: 99%